Strategic map as effective instrument of management of industrial enterprise human capital - Zhukov, S.; Malinoshevska, K. (Економічний вісник Донбасу, 2018)
The article substantiates the formalization of the strategy for the effective use of the human capital enterprise by strategic cards, which are the link between the formulation of the strategy and its implementation. Strategic maps allow us to identify the relationship between the indicators of individual assessment of employees and the complex system of performance indicators of the enterprise, acting as a tool for describing the strategic objectives of each aspect of activity within the framework of a balanced system of indicators. As a result of the introduction of strategic maps, the company has the opportunity not only to analyze and evaluate the results of operations for the past period, but also to effectively manage its activities on the basis of this analysis. У статті обґрунтовано, що формалізацію стратегії ефективного використання людського капіталу підприємства можна здійснювати за допомогою стратегічних карт, які є сполучною ланкою між формулюванням стратегії та її втіленням. Стратегічні карти дозволяють виявити залежність між показниками індивідуальної оцінки працівників і комплексною системою показників діяльності підприємства, виступаючи інструментом опису стратегічних цілей кожного аспекту діяльності в рамках збалансованої системи показників. У результаті впровадження стратегічних карт підприємство одержує можливість не просто аналізувати й оцінювати результати діяльності за минулий період, але й ефективно управляти своєю діяльністю на основі даного аналізу. В статье обосновано, что формализацию стратегии эффективного использования человеческого капитала предприятия можно осуществлять при помощи стратегических карт, которые являются связующим звеном между формулированием стратегии и ее воплощением. Стратегические карты позволяют выявить зависимость между показателями индивидуальной оценки работников и комплексной системой показателей деятельности предприятия, выступая инструментом описания стратегических целей каждого аспекта деятельности в рамках сбалансированной системы показателей. В результате внедрения стратегических карт предприятие получает возможность не просто анализировать и оценивать результаты деятельности за прошлый период, но и эффективно управлять своей деятельностью на основе данного анализа.